2019
DOI: 10.1002/glia.23753
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and sexual differentiation of the developing brain: A focus on ontogeny and intrinsic factors

Abstract: Sexual differentiation of the brain during early development likely underlies the strong sex biases prevalent in many neurological conditions. Mounting evidence indicates that microglia, the innate immune cells of the central nervous system, are intricately involved in these sex‐specific processes of differentiation. In this review, we synthesize literature demonstrating sex differences in microglial number, morphology, transcriptional state, and functionality throughout spatiotemporal development as well as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 128 publications
(227 reference statements)
1
55
1
Order By: Relevance
“…However, studies using different ELS procedures have yielded different outcomes. As previously described by Bordt, Caesrine, and Bilbo (2019), sex differences in microglial number and morphology exist during critical periods of development [167]. These developmental differences may mediate the diverse sex-specific reactivity to ELS [168].…”
Section: Perspectivesmentioning
confidence: 54%
“…However, studies using different ELS procedures have yielded different outcomes. As previously described by Bordt, Caesrine, and Bilbo (2019), sex differences in microglial number and morphology exist during critical periods of development [167]. These developmental differences may mediate the diverse sex-specific reactivity to ELS [168].…”
Section: Perspectivesmentioning
confidence: 54%
“…However, four days later situation is reversed with males display more amoeboid microglia than females in the parietal cortex, hippocampus, and amygdala (Schwarz et al, 2012). However, a few studies to date reported that cerebellum microglia does not demonstrate any sex differences in shape and quantity (reviewed in (reviewed in Bordt, Ceasrine, & Bilbo, 2020; VanRyzin, Pickett, & McCarthy, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Microglia also interact with neurons through physical contact under homeostatic conditions [7,9,11,[33][34][35][36] . Microglia have recently been shown to contact dendrites and neuronal cell bodies in the normal adult brain [37,38] .…”
Section: Introductionmentioning
confidence: 99%